A Quality Improvement Bundle to Improve Informed Choice for Children With Typical, Newly Diagnosed Immune Thrombocytopenia. Issue 8 (November 2018) - Beck, Carolyn E.; Carcao, Manuel; Cada, Michaela; Porter, Stephen; Blanchette, Victor S.; Parkin, Patricia C.
Abstract : IVIG has been the predominant therapy for the initial management of children with newly diagnosed immune thrombocytopenia at our hospital. With current guidelines supporting more conservative management, we undertook a quality improvement initiative to lead practice change. Over a 2-year time period (2013 to 2015), we strove to decrease use of hospital resources (use of IVIG, length of stay) while optimizing family satisfaction. An interdisciplinary working group was struck and a quality improvement bundle was implemented. The bundle comprised a patient information sheet; an evidence-informed, consensus-based protocol; and promotion of shared decision-making via stakeholder engagement and education. Data were collected prospectively; baseline data from a 2007 to 2009 audit were used for comparison. In total, 27 patients were included. Mean initial platelet count was 4×10 9 /L. Bleeding was classified as none or mild in 56% of patients. IVIG use decreased from 88% to 55% of patients, corticosteroid prescription increased from 6% to 15%, and observation increased from 6% to 30% of patients. Hospital length of stay decreased from 47 to 36 hours. Family satisfaction was stable across treatment groups. Through introduction of a quality improvement initiative, we were able to improve family-centered care and decrease use of hospital resources.